Evaluation of removal efficiency of Fe(III) and Al(III) ions in acid sulfate water using agarose-based magnesium oxide composite - Ngoc Xuan Dat Mai; Tan Le-Hoang Doan; Le Nguyen Bao Thu; Bach Thang Phan (Vietnam Journal of Science, Technology and Engineering, 2021)
Agarose/MgO composite adsorbents were developed through interspersing MgO nanoparticles with agarose to create an absorbent. The elimination capacity of the composite towards iron (Fe), aluminium (Al), and arsenate (As) in acid sulfate water was evaluated by means of batch method at room temperature. The constituents of the composite were characterized by thermal gravimetric analysis (TGA). The removal efficiency was determined through inductively coupled plasma (ICP) mass spectrometry. The composite adsorbent exhibited an excellent adsorption capacity towards three types of ions and heavy metals that are found in acid sulfate water. After treating with agarose/MgO, the concentrations of Fe and Al decreased from 60.28 and 604.84 μg/l, respectively, to under 3.42 and 1.78 μg/l, respectively. These exceptional results reveal the potential uses of agarose/MgO composites as adsorbents in the treatment of acid sulfate water. Although the ion concentrations were extremely high in the practical solution, the material still showed the great removal efficiency especially towards the Al ion. The results indicate that the agarose/MgO composite shows potential as a great adsorbent for the elimination of harmful ions and heavy metals from acid sulfate water, especially in water from the Mekong delta region.